C1q/tumor necrosis factor‐related protein‐6 attenuates TNF‐α‐induced apoptosis in salivary acinar cells via AMPK/SIRT1‐modulated miR‐34a‐5p expression. Issue 8 (5th January 2021) - Qu, Ling‐Han; Hong, Xia; Zhang, Yan; Cong, Xin; Xiang, Ruo‐Lan; Mei, Mei; Su, Jia‐Zeng; Wu, Li‐Ling; Yu, Guang‐Yan
Abstract: C1q/tumor necrosis factor‐related protein‐6 (CTRP6) is a newly identified adipokine involved in diverse biological processes. However, its role in salivary glands remains unknown. Here, we demonstrated that CTRP6 was mainly distributed in the nuclei, apicolateral membranes, and cytoplasm of human submandibular glands (SMGs), serous cells of parotid glands, and ducts and apicolateral membranes of serous cells in rats and mice. CTRP6 inhibited the apoptosis rate and reversed the increased levels of cleaved caspase 3, caspase 8, caspase 9, and cytochrome C and the decreased Bcl‐2 expression induced by tumor necrosis factor (TNF)‐α in both SMG‐C6 cells and cultured human SMG tissues. Microarray analysis identified 43 differentially expressed microRNAs (miRNAs) in the SMGs of nonobese diabetic mice. miR‐34a‐5p was selected due to its upregulation by TNF‐α, which was abolished by CTRP6. The miR‐34a‐5p inhibitor promoted whereas the miR‐34a‐5p mimic suppressed the effects of CTRP6 on TNF‐α‐induced apoptosis. CTRP6 increased AMP‐activated protein kinase (AMPK) phosphorylation and reversed TNF‐α‐induced SIRT1 downregulation in salivary cells. AraA, an AMPK inhibitor, reversed the effects of CTRP6 on TNF‐α‐induced alterations in the levels of SIRT1, miR‐34a‐5p, Bcl‐2, and cleaved caspase 3 in vitro and ex vivo, whereas activating AMPK by AICAR reversed the decrease in SIRT1 expression and increase in miR‐34a‐5p expression induced by TNF‐α. Inhibition of SIRT1 by EX527 suppressed the effects of CTRP6 on TNF‐α‐induced changes in miR‐34a‐5p and apoptosis‐related proteins. Our findings indicate that salivary glands are novel sites for CTRP6 synthesis and secretion. CTRP6 protects acinar cells against TNF‐α‐induced apoptosis via AMPK/SIRT1‐modulated miR‐34a‐5p expression. Abstract : CTRP6 protects acinar cells against TNF‐α‐induced apoptosis via AMPK/SIRT1‐modulated miR‐34a‐5p expression.